ANALISIS SOSIODEMOGRAFI, PENGETAHUAN DAN SIKAP IBU HAMIL TERHADAP PENERIMAAN VAKSIN COVID-19 DI WILAYAH KERJA PUSKESMAS RAJADESA KABUPATEN CIAMIS - Ecih Winengsih (LPPM Universitas Abdurrab, 2024)
ABSTRACT The SARS-CoV-2 virus causes the 2019 coronavirus epidemic (COVID-19). Pregnant women are a particularly sensitive population and one of the issues being encountered during the pandemic is connected to COVID-19 incidence in this population. Vaccination is an important tool in the fight against this illness. The study's objective was to examine the demographics, levels of education, and opinions of pregnant women in Ciamis Regency about getting the COVID-19 vaccination at the Rajadesa Community Health Center. This study used a quantitative cross-sectional strategy with a sample size of 167 pregnant women selected by proportionate stratified random selection. Chi-square was used to validate the bivariate data. Analisis multivariat with regression berganda. No significant association was found (p=0.77) between age, employment, or parity with the uptake of the Covid-19 vaccination. Pregnant women's acceptance of the Covid-19 vaccine is correlated with their level of vaccine education and vaccination history (p0.000). Attitude is the most influential factor in determining whether or not pregnant women receive the Covid-19 vaccine; pregnant women with a positive attitude are 13.72 times more likely to receive the vaccine than mothers with a negative attitude, as measured by the odds ratio (OR) value of 13.72. Acceptance of the COVID-19 vaccination is influenced by a number of factors, including sociodemographics (education), knowledge, and attitude of pregnant women, with attitude being the most important one. For further scientific advancement, the researcher proposes doing additional study using mixed methodologies research approaches.